2012
DOI: 10.1111/and.12023
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NOX5 in human teratozoospermia compared to normozoospermia

Abstract: Spermatozoa are capable of producing small amounts of reactive oxygen species (ROS), and sperm in teratozoospermia generate more ROS than sperm in normozoospermia. The source of ROS production in ejaculated human sperm has not been fully clarified. Recently, NADPH oxidase 5 (NOX5) was detected in human sperm, and ROS generation by this enzyme was reported. We investigated the magnitude of NOX5 expression in normozoospermic (n = 12) and teratozoospermic (n = 13) semen samples with different percentages of abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
2
14
0
2
Order By: Relevance
“…These are directly involved in the oxidative balance of spermatozoa with the latter being highly interrelated with peroxidative damage to the sperm cell [40,41]. Furthermore, Ghani et al [42] showed a significantly elevated expression of NOX5, a novel NADPH-oxidase and prime candidate for the ROS production in the acrosomal, equatorial, post-acrosomal regions of abnormal spermatozoa. Moreover, a significant positive correlation was observed between the NOX5 activity and the frequency of sperm with abnormal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…These are directly involved in the oxidative balance of spermatozoa with the latter being highly interrelated with peroxidative damage to the sperm cell [40,41]. Furthermore, Ghani et al [42] showed a significantly elevated expression of NOX5, a novel NADPH-oxidase and prime candidate for the ROS production in the acrosomal, equatorial, post-acrosomal regions of abnormal spermatozoa. Moreover, a significant positive correlation was observed between the NOX5 activity and the frequency of sperm with abnormal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Leucocytes and morphologically abnormal spermatozoa are the main sources of ROS in semen (Garrido, Meseguer, Simon, Pellicer, & Remohi, ). NADPH oxidase 5 (NOX5) was detected as the source of ROS production in ejaculated human spermatozoa (Musset et al., ), and correlations were observed between abnormal sperm morphology and both the percentage of NOX5‐positive spermatozoa and the magnitude of NOX5 expression (Ghani, Keshtgar, Habibagahi, Ghannadi, & Kazeroni, ). Higher levels of seminal ROS and lower antioxidant potential were reported in men with idiopathic infertility than healthy fertile controls (Pasqualotto et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…NOX5 was discovered in 2001 in human testis, uterus, spleen, and lymph node (Banfi et al, 2001;Cheng et al, 2001). Some years later, it was found in equine (Sabeur and Ball, 2007), human (Musset et al, 2012;Ghani et al, 2013) and canine spermatozoa (Setyawan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%